Socio-Demographic Determinants of Women’s Entrepreneurship: A Binary Logistic Regression Analysis - Hadjira Larbi Cherif; Amina Badreddine; Azzeddine Sabri (Business Ethics and Leadership, 2025)

(untitled)
Women’s entrepreneurship represents a critical economic driver for developing nations like Algeria, with significant potential to transform socioeconomic landscapes despite persistent barriers limiting female participation in business activities. This study utilizes data from the sixth round of the Multiple Indicator Cluster Survey (MICS6-2019), filtering a sample of 5,414 working women to investigate socio-demographic and economic determinants of women's entrepreneurial activities in Algeria. It was hypothesized that key socio-demographic factors, including age, marital status, residence, and living standards, influence women’s entrepreneurial inclination; educational level and vocational training significantly determine entrepreneurial participation; and government support programs contribute to increased female entrepreneurship engagement. Using binary logistic regression analysis with JAMOVI statistical software, the research reveals that only 13.2% of working Algerian women engage in entrepreneurial activities, with marital status, age, and educational level emerging as significant determinants. Specifically, married women demonstrate higher entrepreneurial participation than single women, younger women show greater entrepreneurial tendencies than older counterparts, and women with lower educational levels are more likely to pursue entrepreneurship than highly educated women. Contrary to expectations, vocational training, government support programs, wealth index, and geographical location (rural versus urban) did not significantly influence entrepreneurial engagement. This research opens avenues for further investigation into the psychosocial dimensions of women’s entrepreneurship in Algeria and calls for developing targeted interventions that address both structural constraints and individual capabilities to foster a more inclusive entrepreneurial ecosystem.